INTRODUKSI ANEKA PANGANAN RINGAN DARI BUAH SUKUN - Surti Zahra; Angrian Permana; Dini Martinda Lestari; David Elien Simamora; Astri Dewi (Gapenas Publisher, 2021)
Breadfruit is the name of a tree that is found in the village of Lempuyang, especially new breadfruit fruit used to be eaten after steaming or fried. To improve the economy of the lempuyang village community, especially for housewives and young people who do not have income, there needs to be innovation from this breadfruit fruit. The implementation of community service activities in the form of introduction of light food from breadfruit as an effort to utilize the potential of the village to improve the community economy. The introduction process is carried out according to stage 1) the introduction of the benefits of breadfruit, 2) the socialization of the introduction of the process of light food production of breadfruit, and 3) demonstration and direct practice of the production process of breadfruit (Bread Fruit Ketapang), breadfruit chocolate cake (Choco Bread Fruit), breadfruit cake (Original Bread Fruit) and breadfruit wheat cake (Oat Bread Fruit), 4) Seminar. The result of this activity is that the community becomes able to produce light food from breadfruit